Dietary carbohydrate and performance of brief, intense exercise - Walberg Rankin, J. (2000)
A high-intensity exercise bout uses carbohydrate at a very high rate, but the total use is limited due to the brief duration of exercise. Reduction of muscle glycogen during a typical resistance exercise bout or a single 30-s sprint is likely to be in the range of 25-35% of the total glycogen store in the active muscles, whereas repeated sprints will cause a greater drain on glycogen. Muscle glycogen is depleted more rapidly from Type II (fast) than from Type I (slow) fibers during high-intensity exercise. Thus, even when glycogen depletion in mixed muscle fibers is modest, extensive glycogen use by type II fibers as well as selective depletion of glycogen from specific cellular compartments may precipitate fatigue. Performance of a single sprint or of repeated sprints is usually superior after a high-carbohydrate compared to a low-carbohydrate diet. The benefit of high-carbohydrate diets versus moderate-carbohydrate diets for performance of high-intensity exercise has not been clearly shown.